Buying to Sell: A Theory of Buyouts - Pehr-Johan Norbäck; Lars Persson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2010)
Private equity owned firms have more leverage, more intense compensation contracts, and higher productivity than comparable firms. We develop a theory of buyouts in oligopolistic markets that explains these facts. Private equity firms are more aggressive in inducing restructuring compared to incumbents since they maximize a trade sale price. The equilibrium trade sale price increases in restructuring not only by increasing the profit of the acquirer, but also by decreasing the profits of non-acquiring firms. Predictions on the exit mode and on when private equity firms can outbid incumbents in the market for corporate control are also derived.
Keywords: G24; G32; G34; L10; L20; 330; Acquisitions; Buyouts; Buy-to-sell; Buy-to-keep; Leveraged buyouts; Private equity; Take-overs; Temporary ownership; Übernahme; Private Equity; Oligopol; Unternehmenserfolg; Theorie